A Nursing Care A Lemon Aromatherapy Intervenstion to Nausea Vomiting and Sleep Disorder in Pregnancy Women In The Working Area of Putri Ayu Health Center Jambi City - Humaira, Anisa; -, Meinarisa (Jurnal Ilmiah Perawat Manado (Juiperdo), 2024)
Background: Nausea, vomiting and sleep disorders are discomforts that occur during pregnancy. Nausea and vomiting occur due to progesterone hormone levels which also increase the HCG hormone which causes an increase in stomach acid and contraction of the smooth muscles of the digestive tract. Changes in sleep patterns that occur in the first trimester of pregnancy occur starting at 7 weeks due to pressure on the bladder by the enlarging uterus. A study was carried out on lemon aromatherapy as a complementary therapy that can be used to help with these two problems. Objective: This study aimed to provide an applicating of lemon aromatherapy to nausea, vomiting and sleep patterns of pregnant women in the first trimester. Methods: Analysis of case studies showed a reduction in nausea and vomiting after administering the intervention for 7 days. Judging from complaints and PUQE-24 scores which decreased on the first day of intervention with a score of 7 (moderate nausea and vomiting category), on the third day the PUQE-24 score was 3 (mild nausea and vomiting category), on the fifth day with 6 (mild nausea and vomiting) and on the seventh day of intervention a score of 3 (mild nausea and vomiting category). Aromatherapy therapy on pregnant women's sleep patterns was found to help increase pregnant women's sleep hours at night as a relaxing effect. Conclusion: Lemon aromatherapy is effective in helping the problems of nausea, vomiting and sleep patterns of pregnant women in the first trimester. Keywords: Lemon Aromatherapy; Nause and Vomiting; Sleep Disorders, Pregnancy Women